The Governance of Corporate Responsibility: A ‘How to’ Guide - Spitzeck, Heiko (Cranfield University School of Management, 2010)
Imagine a Financial Times reporter asking you critical questions on corporate responsibility (CR) issues of your organisation’s strategy and your governance arrangements for this strategy. How comfortable would you feel being a board member of a CR leader or a laggard? Corporate governance for CR can make a significant difference! This is especially true as CR has become part and parcel of good business and risk management and therefore, should be managed as such.This guide aims to explain how to integrate CR and sustainability issues within the governance framework of an organisation, providing some answers from CR leaders as well as outlining some potential pitfalls. Our recommendations have been compiled from a wide array of reports and academic research (listed in the reference section).